Health information technology in primary health care in developing countries: a literature review. - Tomasi E; Facchini LA; De Fatima Santos Maia M (Bulletin of the World Health Organization, 2004)
This paper explores the debate and initiatives concerning the use of information technology (IT) in primary health care in developing countries. The literature from 1992-2002 was identified from searches of the MEDLINE, Latin American and Caribbean Health Science Literature Database (LILACS), Cochrane Library and Web of Science databases. The search identified 884 references, 350 of which were classified according to the scheme described by the Pan American Health Organization (PAHO). For the analysis of advantages, problems and perspectives of IT applications and systems, 52 articles were selected according to their potential contribution to the primary health-care processes in non-developed countries. These included: 10 on electronic patient registries (EPR), 22 on process and programmatic action evaluation and management systems (PPAEM) and 20 on clinical decision-support systems (CDS). The main advantages, limitations and perspectives are discussed.